Mechanistic Insights into Aging, Cell-Cycle Progression, and Stress Response - Harkness, Troy A. (Frontiers in Physiology, 2012)
The longevity of an organism depends on the health of its cells. Throughout life cells are exposed to numerous intrinsic and extrinsic stresses, such as free radicals, generated through mitochondrial electron transport, and ultraviolet irradiation. The cell has evolved numerous mechanisms to scavenge free radicals and repair damage induced by these insults. One mechanism employed by the yeast Saccharomycescerevisiae to combat stress utilizes the Anaphase Promoting Complex (APC), an essential multi-subunit ubiquitin-protein ligase structurally and functionally conserved from yeast to humans that controls progression through mitosis and G1. We have observed that yeast cells expressing compromised APC subunits are sensitive to multiple stresses and have shorter replicative and chronological lifespans. In a pathway that runs parallel to that regulated by the APC, members of the Forkhead box (Fox) transcription factor family also regulate stress responses. The yeast Fox orthologs Fkh1 and Fkh2 appear to drive the transcription of stress response factors and slow early G1 progression, while the APC seems to regulate chromatin structure, chromosome segregation, and resetting of the transcriptome in early G1. In contrast, under non-stress conditions, the Fkhs play a complex role in cell-cycle progression, partially through activation of the APC. Direct and indirect interactions between the APC and the yeast Fkhs appear to be pivotal for lifespan determination. Here we explore the potential for these interactions to be evolutionarily conserved as a mechanism to balance cell-cycle regulation with stress responses.